On color - Kastan, David Scott; Farthing, Stephen 1950- (Yale University Press, 2018)
"Ranging from Homer to Picasso, and from the Iranian Revolution to The Wizard of Oz, this spirited and radiant book awakens us anew to the role of color in our lives. Our lives are saturated by color. We live in a world of colors, and color marks our psychological and social existence. But for all color's inescapability, we don't know much about it. Authors David Scott Kastan and Stephen Farthing offer a fresh and imaginative exploration of one of the most intriguing and least understood aspects of everyday experience. Kastan and Farthing, a scholar and a painter, investigate color from numerous perspectives: literary, historical, cultural, anthropological, philosophical, art historical, political, and scientific. In ten wide-ranging chapters, each devoted to a different color, they examine the various ways colors have shaped and continue to shape our social and moral imaginations. Each individual color becomes the focal point for a consideration of one of the extraordinary ways in which color appears and matters in our lives. Beautifully produced in full color, this is a remarkably smart, entertaining, and fascinating guide to this elusive topic."--